2017
DOI: 10.1007/s10554-017-1224-x
|View full text |Cite
|
Sign up to set email alerts
|

4D flow image quality with blood pool contrast: a comparison of gadofosveset trisodium and ferumoxytol

Abstract: To evaluate the effect of MRI blood pool contrast agent on 4D flow image quality and ventricular volume measurements. Adult patients referred for clinical cardiac MRI (n = 22) were imaged with 4D flow. Patients with renal failure (n = 10) received ferumoxytol, and the remainder (n = 12) received gadofosveset trisodium. Image quality was assessed with (1) signal-to-noise ratio (SNR); (2) contrast-to-noise ratio (CNR); and (3) 5-point Likert scale based on endocardial border definition (1 = none; 2 = partial but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…To achieve good contrast in conventional clinical 4D flow MRI, contrast agents (such as ferumoxytol and gadolinium) are injected [26]. However, contrast agents have disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve good contrast in conventional clinical 4D flow MRI, contrast agents (such as ferumoxytol and gadolinium) are injected [26]. However, contrast agents have disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…Kamphuis et al found good scanrescan reproducibility of diastolic left ventricular kinetic energy, viscous energy loss, and vorticity assessment [74]. Ferumoxytol was found to be a good alternative to gadofosveset trisodium for 4D flow image quality [75]. Pulse wave velocity calculated from 4D flow of the aorta at 3T and was found to significantly correlated to measures of arterial stiffness determined with transesophageal echocardiography in stroke patients [76].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…This strategy maximizes SNR for vascular luminal visualization and therefore VNR for flow quantification. Iron-based contrast, ferumoxytol, is also effective for maximizing intravascular SNR [8][9][10], though we use this infrequently in adult patients due to logistical hurdles, cost, and inability to provide myocardial delayed enhancement.…”
Section: Contrast and Mramentioning
confidence: 99%